Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

LPBF Manufactured Functionally Graded Lattice Structures Obtained by Graded Density and Hybrid Poisson’s Ratio - Abdelaal, Osama; Hengsbach, Florian; Schaper, Mirko; Hoyer, Kay-Peter (Materials)
The additive manufacturing (AM) of innovative lattice structures with unique mechanical properties has received widespread attention due to the capability of AM processes to fabricate freeform and intricate structures. The most common way to characterize the additively manufactured lattice structures is via the uniaxial compression test. However, although there are many applications for which lattice structures are designed for bending (e.g., sandwich panels cores and some medical implants), limited attention has been paid toward investigating the flexural behavior of metallic AM lattice structures with tunable internal architectures. The purpose of this study was to experimentally investigate the flexural behavior of AM Ti-6Al-4V lattice structures with graded density and hybrid Poisson’s ratio (PR). Four configurations of lattice structure beams with positive, negative, hybrid PR, and a novel hybrid PR with graded density were manufactured via the laser powder bed fusion (LPBF) AM process and tested under four-point bending. The manufacturability, microstructure, micro-hardness, and flexural properties of the lattices were evaluated. During the bending tests, different failure mechanisms were observed, which were highly dependent on the type of lattice geometry. The best response in terms of absorbed energy was obtained for the functionally graded hybrid PR (FGHPR) structure. Both the FGHPR and hybrid PR (HPR) structured showed a 78.7% and 62.9% increase in the absorbed energy, respectively, compared to the positive PR (PPR) structure. This highlights the great potential for FGHPR lattices to be used in protective devices, load-bearing medical implants, and energy-absorbing applications.
Keywords: General Materials Science

On the influence of physical vapor deposited thin coatings on the low-cycle fatigue behavior of additively processed Ti-6Al-7Nb alloy - Hein, Maxwell; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hoyer, Kay-Peter; Tillmann, Wolfgang; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Flow in Pillow-Plate Channels for High-Speed Turbomachinery Heat Exchangers - Sundermeier, Stephan; Passmann, Maximilian; aus der Wiesche, Stefan; Kenig, Eugeny Y. (International Journal of Turbomachinery, Propulsion and Power)
In numerous turbomachinery applications, e.g., in aero-engines with regenerators for improving specific fuel consumption (SFC), heat exchangers with low-pressure loss are required. Pil low-plate heat exchangers (PPHE) are a novel exchanger type and promising candidates for high-speed flow applications due to their smooth profiles avoiding blunt obstacles in the flow path. This work deals with the overall system behavior and gas dynamics of pillow-plate channels. A pillow-plate channel was placed in the test section of a blow-down wind tunnel working with dry air, and compressible flow phenomena were investigated utilizing conventional and focusing schlieren optics; furthermore, static and total pressure measurements were performed. The experiments supported the assumption that the system behavior can be described through a Fanno–Rayleigh flow model. Since only wavy walls with smooth profiles were involved, linearized gas dynamics was able to cover important flow features within the channel. The effects of the wavy wall structures on pressure drop and Mach number distribution within the flow path were investigated, and a good qualitative agreement with theoretical and numerical predictions was found. The present analysis demonstrates that pressure losses in pillow-plate heat exchangers are rather low, although their strong turbulent mixing enables high convective heat transfer coefficients.
Keywords: Mechanical Engineering; Energy Engineering and Power Technology; Aerospace Engineering

State-of-the-Art Modeling of Separation Columns: A Review - Kenig, Eugeny Y. (Chemical Engineering Transactions)

Wässrige Aminozuckerlösungen als neue Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Baumhögger, Elmar; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet Fachgruppen Fluidverfahrenstechnik und Hochdruckverfahrenstechnik)

Flow Morphology of TEG Desiccant in a Structured Packing Air Dehumidifier Exposed to Floating Conditions - Mamedov, Tural; Schleicher, Eckhard; Schubert, Markus; Ehlert, Thomas; Kenig, Eugeny Y.; Hampel, Uwe (Proceedings of the 12th international conference Distillation & Absorption 2022)

Systematic Investigations Concerning Eddy Currents in Additively Manufactured Structures - Haase, Michael; Zimmer, Detmar (Innovative Product Development by Additive Manufacturing 2021)

He’d seen it in the words of Owen and Brooke': Toward a Renaissance of Soldier Poetry in Twenty-First Century Britain - Behler, Felix (ESSE Conference 2022. Seminar: British and Irish Poetry after the Turn of the Millennium: Trends, Public/Counterpublic, Institutions. Organisation: Professor David Malcomb (University of Gdansk), Wolfgang Görtschacher (University of Salzburg))

Configuring the War-Zone: Battlefields as Markers of Glory and Catastrophe in Modern and Contemporary British Literature - Behler, Felix (Artistic Practices of (Un-)Making Place. Organisation: Professor Mihaela Irimia (University of Bukarest), Univ. Professor Christoph Singer (University of Innsbruck), Professor Christoph Ehland (University of Paderborn))

The Iraq and Afghanistan War Memorial - A Landmark Shift in British Memory Culture - Behler, Felix (BRITCULT 2022: British Identities Medialised. Organisation: Univ. Professor Dorothea Flothow, Dr. Sarah Herbe, Assoz. Professor Markus Oppolzer, Dr. Elizabeth Schober (Paris Lodron Universität Salzburg))

Inventing a New Landscape: The Literature(s) of Gardening in 18th-Century-England - Behler, Felix (MLA Convention 2022. Session: Architectural Spaces and the Constitution of Authority in Early Modern European Literature. Organisation: Professor Katherine Brown (Albright College Pennsylvania))

Recapturing ‘Old England’ – Nostalgia, Aristo-Anglophilia, and the Transnational Impact of ITV’s ‘Downton Abbey' - Behler, Felix (Identity and Otherness in Film. Organisation: London Centre for Interdisciplinary Research)

Increasing the accuracy of clinching process simulations by modeling the friction as a function of local joining process parameters - Rossel, Moritz Sebastian; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In this study, an innovative friction model is used to improve the quality of clinching process simulations. Consequently, the future over dimensioning can be reduced. Furthermore, the improved prediction quality of the joining process simulation leads to an improvement in the simulation of load-bearing capacity as well. In this way, the entire sampling process can be performed virtually without any experimental investigations. This will contribute to the advancement of lightweight construction in the automotive industry. In this work, the frictional behavior is studied in dependence on the local joining process parameters. As a reference for the numerical investigations, clinch joints by means of a die with fixed geometry are joined. Additionally, a hardness mapping is performed on the microsection of the clinch joints. It shows the local strain hardening, which correlates with the forming degree in the simulation. Based on the occurring contacts and the local joining process parameters in the joining process simulation, the test matrix for the experimental friction tests is defined. The friction tests are carried out on a compression-torsion-tribometer. This type of tribometer is able to apply high interface pressures above the initial yield stress due to the specimen encapsulation. Besides, the pure joining part contact, the contact between the joining part and joining tool can be tested as well. The experimental test setup offers the possibility to evaluate the influences of temperature, relative velocity, interface pressure, and frictional stroke independently. Based on the results of the experimental friction tests, a friction model is created. The resulting friction model is integrated into the numerical joining process simulation via a subroutine. To validate the quality of the new friction modeling, the results of simulations are compared with the experiments in terms of load-stroke diagrams, joint geometry, and hardness mappings on the microsection.
Keywords: Mechanical Engineering; General Materials Science

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Methodology for the systematic investigation of the hygrothermal-mechanical behavior of a structural epoxy adhesive - Sander, Sascha; Meschut, Gerson; Kroll, U.; Matzenmiller, A. (International Journal of Adhesion and Adhesives)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Model Based and Experimental Analysis of the Dynamic Reactive Absorption Loop Behavior - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Proceedings of the 12th international conference Distillation & Absorption 2022)